Crystal structure of the regulatory subunit H of the V-type ATPase of Saccharomyces cerevisiae - Sagermann, Martin (The National Academy of Sciences, 2001)
In contrast to the F-type ATPases, which use a proton gradient to generate ATP, the V-type enzymes use ATP to actively transport protons into organelles and extracellular compartments. We describe here the structure of the H-subunit (also called Vma13p) of the yeast enzyme. This is the first structure of any component of a V-type ATPase. The H-subunit is not required for assembly but plays an essential regulatory role. Despite the lack of any apparent sequence homology the structure contains five motifs similar to the so-called HEAT or armadillo repeats seen in the importins. A groove, which is occupied in the importins by the peptide that targets proteins for import into the nucleus, is occupied here by the 10 amino-terminal residues of subunit H itself. The structural similarity suggests how subunit H may interact with the ATPase itself or with other proteins. A cleft between the amino- and carboxyl-terminal domains also suggests another possible site of interaction with other factors.